PENDIDIKAN TAUHID DAN AKIDAH PADA ANAK DENGAN MEMBANGUN CINTA PADA ISLAM - Ira Suryani; Lily Sardiani Daulay; Nur Elmi; Ilham Karim Parapat (Institut Dirosat Islamiyah Al-Amien Prenduan, 2019)
Tawhid and creed education are basic education that must be taught to children from an early age. Parents are the most important foundation in a child's behavior and language. This monotheistic education is given with the aim of making children servants of Allah, who will obey all His commandments and prohibitions and become useful people for society and its people. The education that parents can do for their children is through habituation, because children prefer to follow what they see instead of what they hear. Of course, as an example in a child's life, parents must set an example that develops values. tawhid and creed in children so that children can feel the love of Islam within themselves.